Analisis Paparan Publik dan Implikasinya Bagi Individu dengan Narcissistic Personality Disorder: - - asiyah, siti; Fikri, Muhammad Sofi Rijalul; Putri, Qonita Aristawidya; Aliyah, Himmatul; Syahreni, Nabila Dwi; Putri, Selfia Setya; Salsabilah, Sabrina Wahyu; Muhammad, Di-Julieant Xavier (Psikodinamika: Jurnal Literasi Psikologi, 2025)
Tiktok has become a social media that makes it easy to interact. However, apart from presenting educational content, there are potential dangers such as narcissistic personality disorder (NPD) experienced by one of the TikTok users with the initials ALM. This study aims to analyze public exposure and its implications for individuals with NPD. This research uses a qualitative research approach with the ALM behavior analysis method on TikTok videos. The results of this study show that public exposure can worsen narcissistic behavior as happened in the ALM case.